2015
DOI: 10.7150/ijms.13298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Active Mastication on Chronic Stress-Induced Bone Loss in Mice

Abstract: Chronic psychologic stress increases corticosterone levels, which decreases bone density. Active mastication or chewing attenuates stress-induced increases in corticosterone. We evaluated whether active mastication attenuates chronic stress-induced bone loss in mice. Male C57BL/6 (B6) mice were randomly divided into control, stress, and stress/chewing groups. Stress was induced by placing mice in a ventilated restraint tube (60 min, 2x/day, 4 weeks). The stress/chewing group was given a wooden stick to chew du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(45 reference statements)
0
13
1
Order By: Relevance
“…In contrast to our study, decreased bone mass was reported in mice following exposure to chronic mild stress ( Yirmiya et al, 2006 ; Furuzawa et al, 2014 ; Azuma et al, 2015 ; Lertsinthai et al, 2015 ), an accepted stress model for inducing a depressive-like phenotype and increased plasma GC and NE concentrations. Because GCs are established inhibitors of bone formation by increasing osteoblast and decreasing osteoclast apoptosis ( Weinstein et al, 2004 , 1998 ; O'Brien et al, 2004 ), the difference in the HPA axis activity might contribute to the different effects of CSC and chronic mild stress on bone metabolism and formation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, decreased bone mass was reported in mice following exposure to chronic mild stress ( Yirmiya et al, 2006 ; Furuzawa et al, 2014 ; Azuma et al, 2015 ; Lertsinthai et al, 2015 ), an accepted stress model for inducing a depressive-like phenotype and increased plasma GC and NE concentrations. Because GCs are established inhibitors of bone formation by increasing osteoblast and decreasing osteoclast apoptosis ( Weinstein et al, 2004 , 1998 ; O'Brien et al, 2004 ), the difference in the HPA axis activity might contribute to the different effects of CSC and chronic mild stress on bone metabolism and formation.…”
Section: Discussioncontrasting
confidence: 99%
“…Preclinical studies revealed reduced bone mass in murine models of chronic mild stress, in which mice were subjected to a series of mild and unpredictable physical and/or psychological stressors, resulting in a depressive-like phenotype ( Liu and Liu, 2017 ), basal hypercorticism and sympathetic nervous system (SNS) activation ( Azuma et al, 2015 ; Furuzawa et al, 2014 ; Yirmiya et al, 2006 ; Baldock et al, 2014 ). However, these models might have limitations in trying to reflect the situation in PTSD patients, who suffer from hypo- rather than hypercorticism ( Yehuda and Seckl, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic physical and psychological stress has become a major health issue across the world. Both clinical and animal studies have confirmed that stress is an important risk or aggravating factor for several diseases, including hypertension, cardiovascular disease, bone loss, neurodegenerative diseases, and cancer [ 1 5 ]. In fact, females are easier targets of stress compared with males [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chewing is an effective stress-coping behavior 30 - 32 . In humans, gum chewing relieves stress and improves task performance, and in rodents chewing or biting under restraint or immobilization stress ameliorates stress-induced diseases such as gastric ulcer, and osteoporosis, and attenuates stress-induced cognitive and emotional impairment 30 , 33 - 35 . Chewing under restraint stress rescues the increase in plasma corticosterone levels, deficits in spatial learning ability 36 , and suppression of cell proliferation in the hippocampal DG 37 .…”
Section: Introductionmentioning
confidence: 99%